Relationship Social Economic (Family Income) With Stunting - Nuraini, Nanik; Fitriani, Yunita Dyah (Universitas Islam Lamongan, 2021)
The growth and development of children will experience a rapid increase at an early age, from 0 to 5 years as the phase.Golden age3. Socio-economic (Family Income) is low causing poor nutrition so that it affects the growth and development of children. The purpose of this study was to determine the Socio-Economic Relationship (Family Income) with the occurrence of Stunting in Toddler Age Children in Leran Village, Manyar District - Gresik Regency. The method used isÂ analytic with are search designÂ cross sectional. Data were collected directly through observations of mothers who have children under five in Leran Village - Manyar District, Gresik Regency as many as 82 people with the sampling technique simple random. Data analysis used the statistical test of the contingency coefficient =0.05. The results of the study obtained 46 respondents income < UMR (< Rp 4.3 million); 42 (91.3%) experienced stunting and 4 (8.7%) were not stuntingÂ while 36 respondents had income > UMR ; 2 (5.6%) were stunting and 34 (94.4%) were not stunting. The conclusion is that there is a relationship between socio-economic (family income) with the incidence of stunting in children aged under five, it is recommended to increase family income and pay attention to child nutrition.